Stress to stability: Sense of coherence as a buffer against pandemic-related psychological distress - Anita Padmanabhanunni; Tyrone B. Pretorius (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: Identifying protective factors in mental health-related outcomes is crucial, offering insights into the vulnerabilities and strengths individuals harness against psychological distress. There has been limited focus on exploring complex mediation and moderation models, which can uncover the relationships between stressors, protective factors and wellbeing.